2008
DOI: 10.1155/2008/858759
|View full text |Cite
|
Sign up to set email alerts
|

IDE Gene Polymorphism Influences on BPSD in Mild Dementia of Alzheimer's Type

Abstract: Insulin degrading enzyme (IDE) degrades amyloid β (Aβ), which may inhibit the accumulation of Aβ in a brain affected with dementia of Alzheimer's type (DAT). A decrease in the activity of IDE results in changes in glucose utilization in the brain, which could affect the cognitive and psychiatric symptoms of DAT. We investigated a possible association of IDE gene polymorphism and the behavioral and psychological symptoms of dementia (BPSD) in mild DAT. The genotyping for IDE and apolipoprotein E (ApoE) was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In earlier studies, no significant differences were detected for rs1999764 between patients with LOAD and controls in the allele and genotype frequencies, nor were there any associations when data were stratified by APOE∊4 status. 19 21 In contrast, in the present study, an examination of the genotype and allele distribution showed that this SNP is highly linked to LOAD susceptibility, particularly in APOE∊4 noncarriers and female patients (Tables 3 and 4). Thus, further studies on different populations are warranted to identify any possible factors, including ethnic variability, which can account for the discrepancy in these findings.…”
Section: Discussioncontrasting
confidence: 85%
“…In earlier studies, no significant differences were detected for rs1999764 between patients with LOAD and controls in the allele and genotype frequencies, nor were there any associations when data were stratified by APOE∊4 status. 19 21 In contrast, in the present study, an examination of the genotype and allele distribution showed that this SNP is highly linked to LOAD susceptibility, particularly in APOE∊4 noncarriers and female patients (Tables 3 and 4). Thus, further studies on different populations are warranted to identify any possible factors, including ethnic variability, which can account for the discrepancy in these findings.…”
Section: Discussioncontrasting
confidence: 85%
“…Indeed, IDE/HHEX genes have been linked to type 2 diabetes and elevated blood glucose level [ 12 , 13 ]. Although genetic association studies on SNPs in the IDE/HHEX region and AD have produced both positive and negative findings [ 14 ], several studies have suggested that genetic variations within the IDE/HHEX gene region may impact both diseases, and thus underlie the association between diabetes and AD [ 7 ]. So far, no studies have examined the role of IDE/HHEX genes in such an association in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Go et al observed an association between NRG1 SNP, both in isolation and as part of a 3-loci haplotype, and a psychotic phenotype in AD [ 111 ]. Another effort to dissect the genetic background of BPSD focused on the IDE gene coding for insulin-degrading enzyme protein [ 112 ]. The IDE plays a key role in degrading several important peptides, including Aα.…”
Section: Other Genesmentioning
confidence: 99%
“…The IDE plays a key role in degrading several important peptides, including Aα. A correlation was observed between carrying the C allele of the IDE gene and the risk for affective disturbances in AD, with no effect on other behavioural symptoms [ 112 ].…”
Section: Other Genesmentioning
confidence: 99%